Primary Caregivers' Support for Female Family Members With Breast or Gynecologic Cancer. Issue 3 (May 2016) - Han, Jung-Hee; Han, Song-Hee; Lee, Myo-Suk; Kwon, Hye-Jin; Choe, Kwisoon
Abstract : Background: Female patients with cancer depend on loved ones; thus, family support is pivotal to assist patients in successfully adjusting to life with treatment routines. Objective: Our study explored the experiences of primary caregivers who provide care and support for female family members with cancer. Methods: This study used a qualitative phenomenological research approach. Interviews and journaling about the caregiving experience were conducted with the family members of female cancer patients—6 spouses, 11 daughters, 1 son, and 1 younger sister. Data analysis involved Giorgi's 3-step phenomenological analysis method. Results: The central theme of the primary caregivers' supportive care for their female family member with cancer was "being with" her. This was composed of the following themes: "being there for her via efforts, " "living through feelings of guilt and anxiety, " and "lessons learned from cancer in the family." Conclusions: This study reveals an integrated picture of family caregivers' supportive caring experiences. By providing both positive and negative aspects of the caregiving experience, the findings in this study will provide a theoretical foundation to develop more successful support programs for family caregivers of female patients with cancer. Implications for Practice: Family-oriented education programs need to be developed to include both the family and the patient in the long journey of cancer. The family caregivers' feelings of guilt regarding the cause of the illness and feelings of anxiety about the uncertainty of the illness should be assessed and managed during the course of the patients' treatment and care.